Modified Reynolds Equations for Thin Film Lubrication with Saturated High-Viscosity Surface Layer and Lubrication Analysis of Tapered Pad Bearing - Kyosuke Ono (Tribology Online, 2022)
This paper presents a modified Reynolds equation for analyzing thin film lubrication with a saturated high-viscosity surface layer on a solid surface. The saturated high-viscosity characteristics of engine oil blended with additives of metallic detergents and friction modifiers were expressed using new viscosity functions with various orders termed “viscosity model 2,” which is different from the previous model, termed “viscosity model 1.” The viscosity function was then incorporated on the moving surface, and the fluid flow in the bearing gap was determined in a closed-form solution for order numbers N of 2 to 5. Subsequently the modified Reynolds equation was formulated by numerically integrating the flow equation. The modified Reynolds equation was applied to analyze the tapered pad bearing, and different features of the load capacity and friction coefficients from those for viscosity model 1 were clarified. The effects of the order number N, viscosity ratio, bearing length, and high-viscosity layer thickness on the load capacity and friction coefficient were elucidated. It was found that when the order number N was increased to 5, the friction coefficient decreased to a minimal value, subsequently increased to the maximum value, and then decreased to the lowest value with a decrease in the trailing gap.